SELEVER study: Second follow-up survey - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Soutenir l’Exploitation Familiale pour Lancer l’Élevage des Volailles et Valoriser l’Économie Rurale (SELEVER) study was a cluster randomized controlled trial conducted in rural Burkina Faso to evaluate the impact of an integrated agriculture-nutrition intervention on the diets, health, and nutritional status of women and children. The intervention package combined poultry value chain development, women’s empowerment initiatives, and a behavior change communication strategy to promote healthier diets and improved feeding, care, and hygiene practices.